Project-Based Learning Strategy for Enhancing Manufacturing Drawing Techniques Competency Using Cad - Rahmadani, Rahmadani; Fernandes, Erik; Zulfadli, Zulfadli (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2024)
This study aims to evaluate the implementation of the Project-Based Learning (PjBL) model in improving the skills and understanding of students in the Diploma-3 Mechanical Engineering Program. The method used is Classroom Action Research (CAR), conducted in three cycles, each consisting of planning, action, observation, and reflection stages. Each cycle was followed by two face-to-face meetings. Data was collected through tests and analyzed descriptively to measure the improvement in students' learning outcomes. The research findings indicate that the implementation of PjBL is effective in enhancing technical skills, understanding of the material, and collaborative skills among students. The achievement of success indicators improved from 56.67% in Cycle I to 86.67% in Cycle III. PjBL has proven to create more applicable and interactive learning experiences, increase student motivation, and prepare them to face industry challenges. This study concludes that the PjBL model can be more widely applied in vocational education to improve students' practical skills and prepare them to meet the growing demands of the industry.Keywords: D3 Mechanical Engineering Program, Project-Based Learning (PjBL), Skill Improvement